In vitro simulated gastrointestinal digestion impacts bioaccessibility and bioactivity of Sweet orange (Citrus sinensis) phenolic compounds - Gloria Itzel Peña-Vázquez; Maria Teresa Dominguez-Fernández; Bianka Dianey Camacho-Zamora; Marcelo Hernandez-Salazar; Vania Urías-Orona; María-Paz De Peña; Ana Laura de la Garza (Journal of Functional Foods, 2022)
Sweet orange (SO) (Citrus sinensis) is a rich source of polyphenols. However, the bioactivity depends directly on the bioaccessibility affected by biological factors during the digestion process. Therefore, this study was performed in lyophilized SO samples before and after an in vitro digestion to obtain total phenolic content (TPC) by Folin-Ciocalteu assay and characterize its phenolic profile by HPLC-ESI-MS/MS with methanolic extracts. Simulating the passive diffusion of biocompounds, samples were dialyzed after intestinal digestion to obtain bioaccessible phenolic compounds (BPC). Ethanolic extracts were used in 3T3-L1 cell culture. The in vitro digestion process decreased 25% the bioaccessibility of SO polyphenols in the intestinal phase. The most abundant subgroup of polyphenols before and after in vitro digestion were the flavanones, representing more than 86% of TPC. Finally, lipid accumulation in cells induced to undergo adipogenesis and treated with BPC decreased although without significant differences at different concentrations.